Is Information Technology boosting Creativity in Higher Education Institutions during Covid-19? - Mirela Mabić; Dražena Gašpar; Vanja Šimićević (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2021)
The global pandemic of the virus COVID-19 dramatically has impacted Higher Education Institutions (HEIs) in Bosnia and Herzegovina and worldwide. HEIs were forced to switch overnight to online lectures and exams without almost any teachers' and students' preparation and education. After one year of online classes at the University of Mostar (SUM), whether that kind of teaching impacts creativity. In order to find the answer to the research question, the authors used a questionnaire they developed and applied in 2015 to investigate students' perceptions about creativity at the University of Mostar. The research presented in this paper is limited to SUM students who have had online classes since March 2020. The primary research goal is to investigate whether there are any significant changes in students' perceptions of creativity compared to research from 2015. Namely, the authors investigate whether the enhanced use of IT and online platforms (Google Meet, SUMARUM - the University of Mostar's variant of Moodle) affected students' creativity.
Keywords: A2; I23; L86; 330; creativity; higher education institution; information technology; Covid-19